PENGARUH BUDAYA LITERASI TERHADAP HASIL BELAJAR MATERI IDE POKOK KELAS V DI SEKOLAH DASAR - W., Rahmatul Awwaliyah; Mukhlishina, Inanny (Universitas Negeri Medan, 2022)
The ability of students in reading literacy is still low, this is indicated by the decline in student learning outcomes. This study aims to determine the effect of the implementation of literacy culture on the learning outcomes of fifth grade students in learning Indonesian. The target of this research is the students of SDN 1 Paciran class V which is divided into two classes, totaling 28 students in class VA and 28 students in class VB. Using quantitative research methods using experimental research design, namely pre-experimental design, the research design used was control-group design. Prestest Posttest Control Group Design using non-parametric data analysis techniques. In the experimental class, students were given treatment or treatment for reading literacy culture for 15 minutes before learning began, and for the control class they did not give any treatment. The results of this study indicate that there is an influence on student learning outcomes in learning Indonesian between the experimental class and the control class, which is seen from the difference in the average value of the experimental classwhich is higher than the control class.